2002
DOI: 10.1007/s00466-002-0339-6
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and hybrid solutions of diffusion problems within arbitrarily shaped regions via integral transforms

Abstract: Linear diffusion problems defined within irregular multidimensional regions are analytically solved through integral transforms, requiring numerical routines only for integration purposes, when a general functional boundary representation is considered. Auxiliary one-dimensional eigenvalue problems mapping the irregular region are applied with an integral transformation procedure so that the original differential SturmLiouville system gives place to an algebraic eigenvalue problem. The exact analytical inversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Microcontroladores 42, 44, 55 P Padrão 24,25,26,27,70,71,73 Parafuso Estojo 70,71,72,73,74,75 Perfis Formados a Frio 56, 57, 58, 69…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microcontroladores 42, 44, 55 P Padrão 24,25,26,27,70,71,73 Parafuso Estojo 70,71,72,73,74,75 Perfis Formados a Frio 56, 57, 58, 69…”
Section: Resultsmentioning
confidence: 99%
“…The authors conclude the work by stating that the solution's convergence via GITT proved to be excellent and completely in agreement with the reference results. They also concluded that automatic error control and computational cost reduction are hallmarks of GITT for this class of problems.Sphaier and Cotta[27] used GITT to obtain solutions of Sturm-Liouville eigenvalue problems, described by multidimensional partial differential models within irregularly shaped domains. Through integral transformations, the successive elimination of independent variables generates a problem of associated algebraic eigenvalue, solved by algorithms from scientific computational libraries.…”
mentioning
confidence: 99%
“…This methodology uses the General Integral Transform Technique [13][14][15] to handle the nonhomogeneities of the proposed problem, by defining an eigenfunction expansion in terms of a simpler Sturm-Liouville problem of known solution 11-12-22-23 . This methodology can be combined with several analytical methodologies available in the literature 11,12,[17][18][19][20][21] to obtain different solutions for different geometries and different orthogonal coordinate systems. This methodology can be combined with several analytical methodologies available in the literature 11,12,[17][18][19][20][21] to obtain different solutions for different geometries and different orthogonal coordinate systems.…”
Section: Resultsmentioning
confidence: 99%
“…Once the eigenvalues  i and eigenfunctions ψ( i ,x) are obtained, the parameters N i e f i can be easily computed from (16) and (17) and the potential P h may be evaluated at a given position vector x at a given time t.…”
Section: Otc 22578mentioning
confidence: 99%
See 1 more Smart Citation